Age-period-cohort analysis of pancreatitis epidemiological trends from 1990 to 2019 and forecasts for 2044: a systematic analysis from the Global Burden of Disease Study 2019 - Jiang, Wenkai; Du, Yan; Xiang, Caifei; Li, Xin; Zhou, Wence (Frontiers in Public Health, 2023)
Objective: Pancreatitis poses a serious medical problem worldwide. This study aims to explore the epidemiological trends of pancreatitis from 1990 to 2019, analyze the association between disease burden and age, period and birth cohort, and subsequently present a forecast of pancreatitis incidence and deaths. Methods: Epidemiologic data were gathered from the Global Health Data Exchange query tool. Joinpoint regression model was used to calculate the average annual percentage changes (AAPCs). Age-period-cohort analysis was utilized to estimate the independent effects of age, period and birth cohort. We also predicted the global epidemiological trends to 2044. Results: Globally, the incident cases and deaths of pancreatitis increased 1.63- and 1.65-fold from 1990 to 2019, respectively. Joinpoint regression analysis showed that the age-standardized incidence rate (ASIR) and age-standardized death rate (ASDR) decreased over the past three decades. The age effect indicates that older people have higher age-specific incidence and death rates. The period effect on incidence and deaths showed downward trends from 1990 to 2019. The cohort effect demonstrated that incidence and death risk peaked in the earlier birth cohort and were lower in the latest birth cohort. Incident cases and deaths of pancreatitis may significantly increase in the next 25 years. The ASIRs were predicted to slightly increase, while the ASDRs were predicted to decrease. Conclusion: Epidemiologic patterns and trends of pancreatitis across age, period and birth cohort may provide novel insight into public health. Limitations of alcohol use and prevention strategies for pancreatitis are necessary to reduce future burden.